Cyber warriors digital battlefield - Motion Planet (Kuala Lumpur : Motion Planet [distributor])
Digital battlefield, explores the combat zone of the 21st century. Instead of outnumbering the enemy with massive forces and firepower, the armies of the future will outsmart foes with computer technology. Computers will enable troops to assess enemy positions more precisely, attack them more rapidly, and even kill more efficiently. Soldiers of the future will wear digital field gear with a special eyepiece that is an image intensifier for night vision, and a monochrome display connected to a backpack computer containing battlefield maps and tactical information.
Keywords: Armed Forces in motion pictures